1970
DOI: 10.1126/science.167.3924.1501
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Studies with Cyclamate and Related Compounds

Abstract: Cyclamate, cyclohexylamine, N-hydroxycyclohexylamine, and dicyclohexylamine can induce chromosomal damage in human leukocyte cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…About 15 hr before harvest, the antioxidants and carcinogens were added separately in 0.2 ml of 2% bovine-serum albumin. Stoltz (19) observed no significant increase of chromosomal aberrations between 5 and 25 hr of carcinogenic exposure. Just before use all antioxidants 42.0%; and dl-a-tocopherol, 63.2%.…”
mentioning
confidence: 99%
“…About 15 hr before harvest, the antioxidants and carcinogens were added separately in 0.2 ml of 2% bovine-serum albumin. Stoltz (19) observed no significant increase of chromosomal aberrations between 5 and 25 hr of carcinogenic exposure. Just before use all antioxidants 42.0%; and dl-a-tocopherol, 63.2%.…”
mentioning
confidence: 99%
“…However, there are references about genotoxic effects of gliotoxin and verruculogen, secondary metabolites of Aspergillus fumigatus (Golden et al, 1998;Nieminen, 2002;Sabater-Vilar, 2003). In addition, there are data regarding genotoxic effects of dicyclohexilamine, a compound similar to fumagillin, obtained either in in vitro mammalian tests (Stoltz et al, 1970;Kuli}, 2006) or in bacterial mutagenicity tests (Purchase et al, 1978;Mortelmans et al, 1986;Heil, 1996). The abovementioned require further investigations in both in vitro as well as in in vivo mammalian tests systems, even more so as fumagillin, contrary to dicyclohexilamine, has primarily two epoxide structures capable of alkylating proteins involved in the packaging of DNA (Birch and Hussain, 1969) thereby establishing conditions for damaging DNA.…”
Section: Resultsmentioning
confidence: 95%
“…As regarding dicyclohexilamine, which is similar to fumagillin, in a cytogenetic study conducted by Stoltz et al (1970), lymphocytes from human blood samples incubated with dicyclohexilamine sulfate expressed a concentration-depended increase in aberration rate from approximately 6% in the controls to nearly 16% in the experimental groups.…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, investigations of the DNA-damaging effect of dicyclohexylamine in the UMU test and in the DNA synthesis inhibition test in HeLa S3 cells, gave no indication that dicyclohexylamine had a damaging effect on DNA (Heil et al, 1996), which is rather surprising considering that fumagillin has primarily two epoxide structures capable of alkylating proteins involved in the packaging of DNA (Birch and Hussain, 1969) thereby establishing conditions for DNA damage. However, in cytogenetic studies carried out by Stoltz et al (1970) dicyclohexylamine sulfate showed a concentration-depended increase in the aberration rate from approx. 6% in the controls to approx.…”
Section: Discussionmentioning
confidence: 92%
“…The available data referring to genotoxic effects of fumagillin (dicyclohexylamine) obtained by in vitro investigations are equivocal, i.e. either positive (Stoltz et al, 1970;Stanimirovic et al, 1999;Stevanovic et al, 2000) or negative (Purchase et al, 1978;Mortelmans et al, 1986;Heil et al, 1996) and there are no references regarding genotoxic effects of fumagillin in vivo (Toxicological Evaluation, 2000).…”
Section: Discussionmentioning
confidence: 99%